OPTIMIZING COMPUTING IN DISTRIBUTED AI SYSTEMS USING EDGE COMPUTING (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article discusses approaches to optimizing computational processes in distributed artificial intelligence systems based on the Edge concept. Computing. This article analyzes architectural models, load balancing methods, model compression algorithms, and computation orchestration mechanisms between the cloud and edge nodes. Particular attention is paid to reducing latency, conserving network resources, and improving the energy efficiency of AI infrastructures.